Trace metal concentrations in marine prawns off the Malaysian coast - Ismail, Ahmad; Jusoh, Noor Razi; Ghani, Idris A. (Elsevier, 1995)
A preliminary survey of the presence of Cu, Cd, Pb and Zn in 10 species of marine prawns was conducted in 1992 and 1993 along the coastal areas of Mersing, Johore; Kuala Terengganu, Terengganu; Melaka; and Kuala Sepetang, Perak. In general, it was found that the levels of trace metals in most of the samples studied were below the maximum permissible limit of the Food Regulations in Malaysia, with the exception of a few samples collected from the coasts of Melaka and Matang, which contained higher levels of Pb and Cd. These data provide a useful baseline for future reference.